The Economic Effects of the Abolition of Serfdom: Evidence from the Russian Empire - Markevich, Andrei; Zhuravskaya, Ekaterina (American Economic Review, 2018)
We document substantial increases in agricultural productivity, industrial output, and peasants' nutrition in Imperial Russia as a result of the abolition of serfdom in 1861. Before the emancipation, provinces where serfs constituted the majority of agricultural laborers lagged behind provinces that primarily relied on free labor. The emancipation led to a significant but partial catch up. Better incentives of peasants resulting from the cessation of ratchet effect were a likely mechanism behind a relatively fast positive effect of reform on agricultural productivity. The land reform, which instituted communal land tenure after the emancipation, diminished growth in productivity in repartition communes. (JEL J47, N13, N33, N43, N53, Q11)